Protocol for a systematic review on tertiary prevention interventions for patients with stroke in African countries. Issue 9 (13th September 2020) - Kroeber, Eric Sven; Adam, Lucas; Addissie, Adamu; Bauer, Alexander; Frese, Thomas; Kantelhardt, Eva Johanna; Unverzagt, Susanne
Abstract : Introduction: Stroke is one of the common causes of mortality, morbidity and years of life lost worldwide. Baseline research on stroke epidemiology, prevention, acute and rehabilitative interventions in Africa is necessary to approach specific contexts and regional circumstances. Most studies on stroke have been conducted in high-income countries. This protocol describes the methodology to summarise the best available evidence on tertiary preventive strategies like rehabilitation interventions for patients with stroke in African contexts. Methods and analysis: We will include experimental studies and prospective cohort studies conducted in African countries. A protocol has been registered in PROSPERO. Systematic search will include eight electronic databases (MEDLINE, Embase, the Cochrane Library, CINAHL, Cab-Direct, Physiotherapy Evidence Database (PEDro), African Journals Online and African Index Medicus) and the International Clinical Trials Register Platform and base on predefined search terms. We will search from inception of each database and repeat this strategy 3 months prior to review submission. Details of all eligible studies will be extracted and risk of bias for outcomes on global disability or dependence in daily living will be assessed. Main aim of this systematic review is to provide a narrative description of evidence on tertiary prevention strategies (including rehabilitation) for stroke. This description will be visualised in structured tables to aid interpretation of study characteristics, intervention effects and certainty of the evidence. Ethics and dissemination: No ethical approval is necessary. Results will be presented in national and international conferences and published in a peer-reviewed journal. PROSPERO registration number: CRD42020159125.